The Impact of The COVID-19 Pandemic on Elderly Patients Motivation for Complete Dentures Fabrication - Okmes Fadriyanti; Widya Puspita Sari; Embun Irzal (Cakradonya Dental Journal, 2024)
The COVID-19 pandemic has impacted field oral and dental health, including tooth loss issues commonly experienced by the elderly. Treatment using complete dentures is very important to restore function. Motivation is an important factor in the success of creating and using completed denture treatment. The purpose of this study was to determine the impact of the COVID-19 pandemic on the motivation of elderly patients in the fabrication of completed dentures. This research employed a descriptive analytical approach using a cross-sectional design. The research sample was selected using a purposive sampling technique, involving 54 elderly patients who underwent compled dentures fabrication at the Baiturrahmah Dental and Oral Hospital from January to December 2022. The results showed that the was no influence of the COVID-19 pandemic on elderly patients, as reflected in the strong motivation of 26 people (89.7%), moderate motivation of 3 people (10.3%) and there was an influence of the COVID-19 pandemic with a strong motivation value as many as 15 people (60%) and moderate motivation as many as 10 people (40%) and a relationship between the impact of the COVID-19 pandemic on the motivation of elderly patients (p = 0.026). The conclusion of this study shows that elderly patients have a strong motivation to fabricate completed dentures despite challenges posed by the COVID-19 pandemic.